The Carrying Capacity of Nature Tourism in Salapar Hill, Bengkayang Regency, Indonesia - Sarma Siahaan; Reine Suci Wulandari; Rosalia Meida Astrida (Journal of Sylva Indonesiana, 2023)
Salapar Hill is one of the leading natural tourist destinations in Bengkayang Regency. Tourist areas with an excessive number of visitors have implications for tourism activities with environmental sustainability. Identifying the carrying capacity is very important to increase visitor comfort and satisfaction. The research aims to get the value of tourism carrying capacity, physical carrying capacity, real carrying capacity, and effective carrying capacity. The research method uses a quantitative descriptive method with data analysis techniques using the calculations of Sumaraw and Sasmita. The carrying capacity of the tourism environment can determine the maximum number of visits to an area. Physical and area management conditions consider three main actions, namely physical carrying capacity, real carrying capacity, and effective carrying capacity. The results obtained the equation PCC > RCC â‰¥ ECC with a value is 366 > 261 â‰¥ 261. It means that the natural tourism area of Salapar Hill has a large carrying capacity to accommodate the number of tourists every day